Keabsahan Imam Salat yang Belum Balig (Studi Komparatif Pendapat Mazhab Syafii dan Mazhab Hanafi) - Muhammad Hanif Hasan; Muhammad Yusram; Irsyad Rafi (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2023)
This study aims to determine the views of the Shafii and Hanafi schools on the validity of prayer imams who have not yet reached puberty, as well as to find out more about the differences in opinions of scholars from these two schools on the matter. The type of research used is qualitative descriptive research, which focuses on the study of manuscripts and texts using normative juridical approach methods and is supported by comparative approach methods. From the results of this study, it was found that the Shafii school punishes the legitimate imam of prayer who has not yet reached puberty who is mumayiz, both in the obligatory prayer and the Sunah prayer, because his ablution is considered valid and there is no problem if a makmum salat is obliged to follow the imam whose essence is the Sunah prayer. According to the Hanafi school, it is not legal for an imam to pray who has not reached puberty even though he has been mumayiz, because the position of the imam demands responsibility and guarantee, while a person who has not yet reached puberty is not included in the group that receives guarantee.